Optimization of Methyl Chloride Production from Methanol and Hydrogen Chloride by Enhancing Purity and Reducing Total Energy Demand - Salsabila, Elvira; Aisyah, Friska Auliya; Zulfa D, Indana; Cahyani, Regita Saalum; Chinara, Nadzwa Adzlia (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Methyl chloride, also known as chloromethane, is an important basic material in the global chemical industry. In 2022, the demand for methyl chloride in Indonesia was recorded at 103,748 tons per year. Based on projections, this figure is expected to increase to 134,696 tons per year by 2027. This study aims to investigate the design of methyl chloride plant by considering the efficiency in terms of energy and purity of yield by utilizing Aspen HYSYS V12 simulation tool in process integration. This research utilizes the iterative simulation method to compare the basic process simulation and the modified process simulation for methyl chloride production. The results show that the modified methyl chloride production process simulation has high energy efficiency as indicated by less energy requirements compared to the basic methyl chloride process. In addition, the simulation results of the modified methyl chloride production process produced methyl chloride reaching a high percentage of purity. In the basic process, the purity of methyl chloride reached 72.36% while the modified process showed an increase to 79.51%. It can be concluded that the simulation results of the modified process are more effective than the basic process in terms of energy requirements and purity product. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).